Exploring Household Food Dynamics During the COVID-19 Pandemic in Morocco - El Bilali, Hamid; Ben Hassen, Tarek; Baya Chatti, Chedli; Abouabdillah, Aziz; Alaoui, Si Bennasseur (Frontiers in Nutrition, 2021)
Alongside the dramatic impact on health systems, eating, shopping, and other food-related habits may have been influenced by the COVID-19 crisis. This paper analyses the impacts of the COVID-19 pandemic on food shopping habits and food-related activities of a diverse sample of 340 adult consumers in Morocco. The study is based on an online survey conducted in Morocco from September 15 to November 5, 2020, utilizing a standardized questionnaire delivered in French and Arabic via Survey Monkey. The findings show that consumers’ diet, shopping behavior, and food interactions have changed significantly. Indeed, the survey outcomes indicated (i) an increase in the consumption of local items owing to food safety concerns; (ii) an increase in online grocery shopping; (iii) a rise in panic buying and food hoarding; and (iv) an increase in culinary capabilities. The findings are expected to help guide Morocco’s current emergency measures as well as long-term food-related policies.